Tick-borne encephalitis in the Åland Islands, Finland: incidence and disease course since the implementation of a general TBE vaccination programme - Tikkala, Jessica; Jansson, Christian; Häggblom, Gunilla; Ringbom, Malin; Grunér, Mathias; Nyman, Dag; Pitkäpaasi, Marjaana; Sjöwall, Johanna; Nordberg, Marika (Taylor & Francis, 2026)
Tick-borne encephalitis (TBE) is a potentially life-threatening viral disease with rising incidence in Europe. This retrospective study investigates the incidence, clinical course, and long-term outcome of TBE in Åland, a region endemic for the disease, following the introduction of a TBE vaccination programme in 2006.
All patients diagnosed with TBE in Åland between 2006 and 2023, in accordance with the diagnostic criteria established by the European Centre for Disease Prevention and Control (ECDC), were included in the study. A review of medical records was conducted, and epidemiological and laboratory data were systematically collected. Disease severity and clinical outcome were assessed.
TBE was diagnosed in 145 patients (66% male; median age 53 years; 10% children <18 years). The median TBE incidence was 29/100,000/year. Primary care was the first point of contact in 48% of cases. Of all patients, 72 (50%) were unvaccinated, 46 (32%) incompletely vaccinated and 20 (14%) completely vaccinated. Fifty-seven (39%) were diagnosed with meningitis and 88 (61%) with meningoencephalitis. Overall, 117/145 (81%) patients were hospitalised and 13/145 (9%) required intensive care. Severity of disease correlated with increasing age. Two fatalities occurred.
Unlike neighbouring regions, Åland did not experience an increase in TBE incidence, likely due to the implementation of the vaccination programme. Most disease courses were monophasic and occurred in unvaccinated individuals. Surprisingly, a significant number of breakthrough infections were observed, particularly among those with incomplete vaccination, who more frequently developed severe disease. However, at two-year follow-up, 86% of patients were considered clinically recovered.